The firm level impacts of local public funding to microenterprises - Saarela, M.; Jokela, H.; Niinikoski, E.; Muhos, M.; Leviakangas, Pekka (2016)
© 2016 Inderscience Enterprises Ltd.In Europe, the public sector allocates a significant amount of resources to entrepreneurship support through subsidies and public advisory services. Typically, public entrepreneurship support is provided without any expectation of direct returns. However, there is a lack of information about the efficiency and effectiveness of these actions. Entrepreneurs in northern sparsely populated areas face context-specific challenges as they operate in the market. The purpose of this study is to investigate the impacts of local action group funding to microenterprises in a northern sparsely populated area. This is a retrospective, single-case study focusing on a sparsely populated area in Northern Finland. The study is based on 25 semi-structured enterprise interviews. Multiple perspectives are analysed in the interviews. This study investigates what the influence was of public local rural financial support from microenterprise entrepreneurs' perspectives. As a result of this case study, the role of public business advisory services for the entrepreneurs in local rural funding process is also clarified. Results can contribute to the effectiveness of public business subsidies, improving the processes to correspond more effectively to case-specific needs of microenterprises.